Elementos compatibles de orden superior para el analisis de flexón de placas - Acuña, Jack López (1972)
The present work deals with the programming of subroutines to calculates the structural properties of compatible elements to the analyses of plates by the Finite Element Method. The first of these elements - R16 - has a rectangular shape and 16 degrees of freedom, and the second, with a triangular shape - T18 - has the 18 degrees of freedom. Different alternatives to obtain the structural properties of these compatible elements are shown. In the case of the R16 element; are presented the structural properties for orthotropic materials, extending in this manner the original work, in which such element was presented. Numerical results are shown, besides the necessary requirements of acuracy to obtain satisfactory results are indicated.